(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Early knowledge about the quality of human resources in North Sumatra Province is essential to enhance the effectiveness of human resource development plans, thereby contributing to equitable improvements in community welfare. This study employs an indicator-based approach to analyze human resource quality across all regencies and cities in North Sumatra Province. These indicators represent four fundamental aspects of strengthening human capital: education, health, housing environment, and employment. The study utilizes secondary data obtained from official publications of relevant institutions. Exploratory Factor Analysis (EFA) is employed to identify the key factors determining human resource quality in North Sumatra Province. The results of the EFA are then used Cluster Analysis to group regencies/cities based on similarities in human resource quality characteristics. The findings reveal two primary factors influencing human resource quality in North Sumatra Province: (1) socio-economic resilience and (2) socio-economic participation. The regencies and cities can be categorized into five distinct clusters based on these determining factors.